The effect of toothpaste containing bacteriocin extract in the growth of streptococcus mutans in vitro - Albesa, Jean Mitchelle P.
Introduction. Over the years, developments in research have geared up towards finding more preventive and less aggressive approaches against dental caries. Treatments are recently directed towards etiological agents, particularly, Streptococcus mutans. Bacteriocins have been known to inhibit bacterial growth in conditions where competition against susceptible bacteria of the same or closely-related species exists.The purpose of this study is to determine the effect of toothpaste containing bacteriocin extract on the growth of Streptococcus mutansin vitro. This study aims to show if toothpaste can deliver that effect of bacteriocin on the growth of Streptococcus mutans in vitro at a given time of exposure. If proven effective, this toothpaste could be recommended as an alternative to reduce the prevalence of dental caries.